Propriedade intelectual por indicação geográfica: O caso da cachaça do Brejo paraibano. - Rocha, Elaine de Lima (2016)
The intellectual property protection ensures the ownership and rights to creators and other producers of intellectual goods and services in what concerns to the elements of knowledge and information. The geographical indication, is a constituent part of the intellectual property rights, it protects goods or services with characteristics attributed to their geographical origin, such as reputation, quality and tradition. The main goal of this work was to verify the perception of the Brejo Paraibano cachaça producers with regard to obtaining the geographical indication seal. The case study methodology was applied to achieve the goal. The research data was collected and analyzed through qualitative research techniques, such as interviews and documentary analysis. The research targeted the producers of cachaça from the Brejo Paraibano micro region. The methodological instrument used in the data analysis process was the content analysis in three chronological poles: pre-analysis; exploration of the material; treatment of the results, inference and interpretation. With regard to the results, it was possible to verify that the researched sugar cane mills produce cachaça in the traditional way, preserving its identity, even when seeking modernization through technology. The producers highlight this identity and claim that consumers attribute quality to the product as a result of belonging to that specific territory. The producers also mention that there is a differential for the characteristics peculiar to the region. It was clearly observed the producers interest in obtaining the geographical indication seal to add value to the product and to strengthen the whole sector. Even though the producers do not possess an in-depth knowledge about the topic, they believe that the Brejo Paraibano micro Region has the necessary attributes for recognition. In order to achieve that, it is essential that producers and actors involved in the process cooperate with each other. However, the region's culture is not favorable to cooperation, being necessary a process to raise awareness among producers. Finally, the study aimed to contribute to the enrichment, enhancement and dissemination of the geographical indication theme in Brazil, with the intention to contribute to the protection of regional culture and tradition.